Carbon paste electrodes in potentiometry: the state of the art and applications in modern electroanalysis (a review) - Stanić, Zorka; Girousi, Stella (Univerzita Pardubice, 2011)
The development of chemical sensors has received widespread attention during the past two decades because of their extensive use in environmental monitoring and clinical analysis via rapid, accurate, reproducible, and low-cost methods. The data reported in literature demonstrate that carbon paste electrodes (CPEs) are very suitable for a variety of applications and many works have thus been devoted to developing new ion-selective electrodes based on carbon paste as the electrode material of choice. Chemically modified CPEs have frequently been employed as potentiometric sensors in trace analysis for metal ions, organic pollutants and biological substances. Most of these electrodes are operated via the ion-exchange process of the active component incorporated into the carbon paste matrix. This review article concentrates on such achievements in the context of the general development across the field.
Keywords: potentiometry; ion-selective electrodes; carbon paste; applications; review